Estimation of transient heat transfer and fluid flow for alloy solidification in a rectangular cavity with an isothermal sidewall. (14th August 2015) - Plotkowski, A.; Fezi, K.; Krane, M. J. M.
Abstract : Transient scaling and integral analyses were performed to predict trends in alloy solidification in a rectangular cavity cooled by an isothermal sidewall. The natural convection fluid flow was approximated by a scaling analysis for a laminar boundary layer at the solidification front, and was coupled to scaling and integral analyses of the energy equation to predict the solidification behaviour of the system. These analyses predicted several relevant aspects of the solidification process, including the time required to extinguish the initial superheat and the maximum local solidification time as a function of the system parameters and material properties. These results were verified by comparison to numerical simulations for an Al–4.5 wt% Cu alloy for various initial and boundary conditions and cavity aspect ratios. The analysis was compared to previous attempts to analyse similar fluid flow and solidification processes, and the limitations of the assumptions used for this analysis were discussed.